According to arden's theorem, we can directly find the answer is QP* Arden's Theorem Statement:
Let $P$ and $Q$ be two regular expressions.
If $P$ does not contain null string, then $R = Q + RP$ has a unique solution that is $R = Qp*$
Proof:
$R=Q+(Q+RP)P$ [After putting the value $R=Q+RP$]
$=Q+QP+RP^{2}$
When we put the value of $R$ recursively again and again, we get the following equation:
$R=Q+QP+QP^{2}+QP^{3}....$
$R=Q(\epsilon +P+P^{2}+P^{3}+....)$
$ R=QP^{*} [ P^{*} = (\epsilon +P+P^{2}+P^{3}+....)] $